Assessment of the utilization rate of organic and nitrogenated substrates by the microorganisms in a sequencing batch reactor treating tannery wastewater - Freytez-Boggio, Estefania; Márquez-Romance, Adriana Mercedes; Barrazueta-Rojas, Sandra Gabriela; Guevara-Pérez, Edilberto (Tecnología y ciencias del agua, 2023)
In this article, the utilization rate of organic and nitrogenous substrates contained in tannery wastewater by a sequential batch reactor is evaluated. Two factorial experimental designs (FEDs) were implemented. FED1 (22) used granular biomass, the aeration sequence (oxic, anaerobic-oxic) and cycle duration (6 and 24 h). FED2 (4 x 3) included suspended biomass, reaction phases (anoxic I, oxic, anoxic II (CND: conventional nitrification-denitrification) and (SND: simultaneous nitrification-denitrification), filling time (fast, slow and in stages). The substrates examined were chemical oxygen demand (COD), ammonium (NH4+-N) and total nitrogen Kjeldahl (TKN). The utilization rates were COD (-100 and -200 mg l-1 h-1) (FED1) and (-48 and -75 mg l-1 h-1) (FED2), being 1.5 to 2 times higher in FED1 than FED2. In TKN (-5 mg l-1 h-1), and NH4+-N (-30 mg l-1 h-1), they were significant in the anoxic I and oxic phases.